Problem of work - "Hubbard,L.Ron" (Los Angels, 2007)
This title contains the senior principles and laws which apply to every endeavor, every problem of work. For they are the discoveries which lay bare the core of these problems and explain the very fabric of life itself. Life is composed of seven-tenths work, one-tenth familial, one-tenth political and one-tenth relaxation. Here, then, is Scientology applied to that seven-tenths of existence including the answers to exhaustion and the secret of efficiency. Here, too, is the analysis of life itself -- a game composed of exact rules. Know them and you succeed. This book contains technology no one can live without, and that can immediately be applied by both the Scientologist and those new to the subject.
Keywords: Scientology